Student acceptance towards AsepticTech VR: a teaching and learning tool for cell and tissue culture aseptic techniques - Cheng Wei, Lim; Kong Yen, Liew; Sie Hui, Lim; Manraj Singh, Cheema; Puteri Suhaiza, Sulaiman; Hanis Hazeera, Harith; Hasni Idayu, Saidi; Chau Ling, Tham (Springer, 2024)
The high cost of establishing a cell and tissue culture facility has denied students an opportunity to practice proper aseptic techniques during their studies. An inhouse application named AsepticTech Virtual Reality (VR) was developed to simulate a cell and tissue culture facility for students to train their aseptic techniques virtually. However, the performance gain associated with the application will be limited by the student’s willingness to use the application. Therefore, this study aims to investigate the driving factors behind students’ intention to use AsepticTech VR. A total of 55 biomedical undergraduates were granted access to AsepticTech VR. After using the application, the students completed a Technology Acceptance Model (TAM) questionnaire. It measures seven latent constructs that are believed to influence the students’ behavioral intention to use the application, namely Perceived Usefulness (PU), Perceived Ease of Use (PEU), Attitude Towards Use (ATU), Behavioral Intention (BI), Perceived Enjoyment (PENJ), Perceived Health Risk (PHR) and Self-Efficacy (SE). The questionnaire was preliminarily evaluated on its validity and reliability using Confirmatory Factor Analysis (CFA), Average Variance Extracted (AVE), Composite Reliability (CR), and Cronbach’s alpha. Subsequently, the interactions between the seven latent variables were analyzed via path analysis. Findings of the path analysis suggested that ATU is the most influential factor on BI, followed by PENJ and SE. In turn, ATU was positively and significantly influenced by PENJ, whereas PHR exerted a significant negative influence on ATU. This study revealed that enjoyment and comfort are the principal factors influencing students’ acceptance of AsepticTech VR. This study also identifies other determinants that influence users’ acceptance of AsepticTech VR and paves guidance for the future development of the application.